An Overview of Knowledge Management in Early Childhood Education for Sustainable Education - Siti Sarah, Sukor; Zuraina, Ali (IOP Publishing, 2021)
This paper presents a review of the current trends in Knowledge Management (KM) implementation for sustainable education. The review includes critical and analytical discussions on the extent of KM at early childhood education (ECE) level. The search of the papers that were included in the review used keywords strings that are related to KM at early childhood education through three (3) phases of review processes namely identification, screening and eligibility. Content analysis was employed as data analysis method. This paper presents some recommendations for future researchers to include three (3) critical components: team work, ICT and training in KM for education to achieve a comprehensive sustainable early childhood education.